2019
DOI: 10.1039/c9nr04464g
|View full text |Cite|
|
Sign up to set email alerts
|

Biosynthesized silver nanorings as a highly efficient and selective electrocatalysts for CO2 reduction

Abstract: Numerous amino acids on protein effectively enhance the reaction activity and selectivity for CO2 electroreduction to CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The results have shown that the size distribution of NPs is uniform and particle agglomeration was avoided. The same group also synthesized Ag nanorings surrounding the outer surface of TMV cp by a fast photoreduction method [47,99] . Ag precursors were first incubated with protein in water at room temperature.…”
Section: Bio‐templates For the Synthesis Of Mnmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results have shown that the size distribution of NPs is uniform and particle agglomeration was avoided. The same group also synthesized Ag nanorings surrounding the outer surface of TMV cp by a fast photoreduction method [47,99] . Ag precursors were first incubated with protein in water at room temperature.…”
Section: Bio‐templates For the Synthesis Of Mnmsmentioning
confidence: 99%
“…In the available literature, bio‐templated MNMs are rarely used in CO 2 RR, which gives future opportunity to explore such an application. Very recently, our group reported the first example of using biosynthesized Ag nanorings for CO 2 RR [99] . A mixture of AgNO 3 and the disk assembly of TMV coat protein was illuminated by UV light, resulting in Ag nanorings assembled on the outer surface of the protein.…”
Section: Applications Of Bio‐templated Mnms For Different Electrocatamentioning
confidence: 99%
See 1 more Smart Citation
“…Noble-metal nanoparticles (NPs) are one of the most well-studied nanomaterials because of their well-controlled preparation and attractive catalytic and optical properties, which originate from their plasmonic properties. Plasmons are collective oscillations of free electrons under irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18–20 ] A series of Ag‐based nanowires (Ag‐NWs) has been prepared as electrocatalysts for CO 2 ‐to‐CO reduction, which achieved high Faradaic efficiencies (FEs), mostly due to the increased electrochemically active surface area. [ 21–23 ] Mauzeroll and coworkers biosynthesized Ag‐based nanorings (Ag‐NRs), which could reach an FE of 95.0% for the conversion of CO 2 to CO. [ 24 ] Polyansky's group reported a Ag nanocoral catalyst with a high surface area, displaying a low overpotential of 0.37 V and high current efficiency of 95% for CO 2 ‐to‐CO reduction catalysis. [ 25 ] In addition, some other nanoporous Ag‐based (np‐Ag) catalysts with diverse nanostructures have also been investigated for electrochemically reducing CO 2 to CO with significantly enhanced catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%